Intention and factors associated with initiation and actual breastfeeding practices among post elective-caesarean delivery women in Kelantan : a prospective cohort study - Johar, Nazirah (2020)
Caesarean delivery is found to be a significant factor for low breastfeeding intention, initiation and exclusive breastfeeding (EBF) practice for six months duration. This study aimed to determine the intention and factors associated with breastfeeding initiation and actual breastfeeding practices among post-elective caesarean delivery women in Kelantan. It employed a prospective cohort study design. A total of 171 women admitted for elective caesarean delivery at two tertiary hospitals in Kelantan participated in this study. A set of structured questionnaires was used to obtain the variables of interest. 77.2% of respondents had a very strong/strong strength of intention to breastfeed their infant before caesarean delivery. After caesarean delivery, 73.7% of women initiated breastfeeding within one hour and it was significantly associated with women who were not sure that their infant looked sleepy (OR 0.40, 95% CI : 0.03, 5.83), infants who received skin to skin contact (OR 14.42, 95% CI:3.58, 58.06) and women who practiced EBF during hospitalization (OR 36.37, 95% CI :5.60, 236.24). The proportion of EBF at one, three, and six months was 80.1%, 59.6%, and 42.0% respectively. Factors found to be associated with non exclusive breastfeeding (NEBF) practice at one month were women last child age between less than two years to more than five years, women who did not practice EBF for her last child (OR 3.78, 95% CI: 1.39, 10.29) and women who never felt confident that her breast milk is adequate (OR 4.83, 95% CI: 1.06,21.96). At three months, factors associated with NEBF practice were women who did not practice EBF for her last child (OR 3.72, 5% CI: 1.69, 8.16) and women who were very often/often perceived no milk (OR 4.97, 95% CI : 1.67, 14.85). At six months, factors associated with NEBF practice were women who were very often/often perceived no milk (OR 10.6, 95% CI : 2.41, 41.99), women who were sometimes/seldom experienced cracked nipples (OR 0.21, 95% CI : 0.06, 0.72) and very often/often experienced breast pain when baby suckled ( OR 4.74, 95% CI: 1.09, 20.56). The women who had very strong/strong strengh of breastfeeding intention before caesarean delivery was relatively high, however proportion of women who initiated breastfeeding within one hour was still unsatisfactory. The prevalence of women who exclusively breastfed their infants was reduced as the child grew older. Therefore, continuous education by health practitioners started from the antenatal period is important to improve breastfeeding intention and to sustain the EBF practice until six months.